The transformation of electoral system in Post-Soviet Georgia - Tetradze, Lia (Politics / პოლიტიკა, 2019)
This paper deals with the issues of transformation of the electoral system of Georgia since 1990 to present. The issues of political parties' representation at the supreme legislative body based on the results of the parliamentary elections at various times are also discussed. There are used the legal sources as well as the opinions of different political actors and representatives of non-governmental organizations and etc.
Keywords: Electoral system, parties, election, transformation, representation